DISTRIBUTION OF INHERITANCE BASED ON INHERITANCE LAWS THAT APPLY IN INDONESIA A STUDY OF THE EXISTENCE OF A SUBSTITUTE INHERITANCE (PLAATSVERVULLING) - Intan Whetaning Mentari; Zainal Arifin (Dinamika Hukum & Masyarakat, 2022)
Abstract The law of inheritance is a series of provisions in which in connection with the death of a person, the consequences in the material field are regulated, namely: the result of the transfer of inheritance from a deceased person to an heir, both in their relationship between themselves and with a third party. The inheritance law system in Indonesia still has a plurality of legal arrangements, among others, there are three inheritance law systems that are valid and accepted by the Indonesian people, namely for native Indonesian citizens the customary inheritance law is still in effect which is regulated according to the composition of the customary community, which is patrilineal, matrilineal and parental / bilateral. In addition, Muslim families carry out inheritance in accordance with Islamic inheritance law. While some people use civil inheritance law. This type of research used in writing this thesis is normative legal research that focuses on positive law. Normative legal research is research that uses statutory analysis as primary legal material. The primary legal material is also supported by books, expert opinion, mass media, newspapers and magazines as secondary legal materials. Because our country adheres to positive law, in other words we obey and obey a set of principles and rules of written law that are currently in force and are binding in general or specifically and must be enforced. In this case the distribution of inheritance can be carried out based on Customary Law, Islamic Law and the Civil Code, therefore for the distribution of inheritance it must remain in the corridor of each law, here we discuss this inheritance problem using Permendagri No. 52 of 2014 concerning Guidelines for the Recognition and Protection of Indigenous Law Communities, Presidential Instruction Number 1 of 1991 concerning Compilation of Islamic Law and the Civil Code. Keywords: customary inheritance law, Islamic inheritance law, civil inheritance law.